Cognitive biases, Robo advisor and investment decision psychology: An investor's perspective from New York stock exchange - Usman Ahmad; Maurice Van Keulen; Alexia Briassouli; Muhammad Saad (Acta Psychologica)
Investment decision making is a systematic process that becomes complex due to cognitive biases and risk perceptions. For rational investment decision making, the investors in the New York Stock Exchange (NYSE) tend to seek automated investment solutions through Robo Advisors and the volume of such trades is mounting. However, there is dearth of studies that depict the role of cognitive biases, Robo Advisor and risk perception in investment decision psychology. Therefore, this study aims to empirically investigate the impact of cognitive biases on investment decision making of investors with the underlying role of risk perception and moderating role of Robo Advisors. The study applies the time lag research design to analyze the mediation and moderation conceptual model through structural equation modeling by using SMART PLS. The data is collected through survey questionnaire from individual investors who trade at NYSE. The empirical findings of structural equation modeling revealed that availability, price anchoring, loss aversion, representative and overconfidence bias impact the risk perception, and the investment decision making. Furthermore, Robo Advisor significantly moderates the relationship between all the cognitive biases and investment decision making, except for overconfidence bias. In addition, this research provides novel contributions to the theory as it links cognitive biases with investment decision through risk perception that develops an underlying mechanism to channelize the impact of cognitive biases on investment decision making. Likewise, inclusion of robo-advisors highlights the crucial role that contributes to weakening the adverse effect of cognitive biases on investment decision making in technology driven financial market. The results are valuable for investors as they get a clear vision of the impact of biases and risk perception during their investment decision making. This research also suggests that investors should use Robo Advisor to minimize their investment risk and to overcome the impact of cognitive biases in their investment decisions.